Agronet : uma plataforma para gerenciamento de dados na agricultura de precisão - Karrei, Mauricio Alex Zientarski (2017)
Technology applied to agriculture generates a large amount of data from different sources, locations and formats. The interpretation of these data can help in the management of the crops, supporting in the reduction in the use of inputs and in the increase in the quantity and the quality of the production. However, analyzing and proposing strategies to manipulate the large amount of data generated by sensors and agricultural electronic devices are often pointed out as some of the key challenges for Precision Agriculture. Therefore, the research carried out in this work aimed the development of a computational platform capable of receiving, processing and making available data from Precision Agriculture. As a result, we obtained a platform and a set of tools that allow the storage and retrieval of large amounts of data, in the space/geo/temporal format. This platform allows, through a REST API, the data manipulation of machinery, implements, sensors and agricultural electronic devices, as well as the manipulation of geospatial data. In order to validate the platform and its tools, a textit web interface has been developed for access and manipulation of the platform data in a visual way.